Dinamika Konflik Pembangunan Bendungan Bener di Desa Wadas: Analisis Video Dokumenter ‘Wadas Waras’ - Khairunissa Aura Fatimah; Sellya Saraswati Dewi; Ayu Awalinda Khoirun Niswati; Dewi Nawang Wulan; Siti Nur Arifatun Nissa; Didi Pramono (Terang : Jurnal Kajian Ilmu Sosial, Politik dan Hukum, 2024)
The study focuses on the construction conflict of the Bendungan Bener in Desa Wadas. The aim of the study is to provide an overview of the Desa Wadas community as well as to analyze the conflict taking place using conflict theory by Ralf Dahrendorf. This research is carried out using a qualitative approach that aims to provide a description of the theoretical analysis of a phenomenon in a holistic and in-depth manner. Research data is obtained using documentation study techniques and library studies supported by relevant sources. Based on the analysis of Ralf Dahrendorf's conflict theory, the results of this study explain that the Bendungan Bener construction conflict is an inter-class conflict in which the society as an impotent group is harmed and the government as a powerful group has hidden interests. This research can have implications both internally and externally. Internally, this research can be research material for researchers in analyzing inter-class conflict in society. Externally, it can be a reference for relevant parties who have the same subject of research.